Features of urban food and nutrition security and considerations for successful urban programming - Ruel, Marie T.; Garrett, James L. (Food and Agriculture Organization of the United Nations, 2004)
This paper updates our earlier reviews of urban food and nutrition security (Ruel, Haddad and Garrett, 1999; Ruel et al., 1998). These earlier pieces reviewed existing knowledge from published literature concerning the unique characteristics of urban food and nutrition security and their determinants, and experience of successful programme and policy responses to alleviate urban food insecurity and malnutrition. The reviews also identified key research gaps. The present review focuses more on what we have learned on these issues from five years of empirical research and through our collaboration with partners directly involved in the design and implementation of urban programmes in the field. CARE International and some of their country offices have been our main partners to date, and we have also collaborated with the Government of Guatemala in the evaluation of a community day care programme. Our research programme combined primary data collection in a number of countries and secondary analysis of data from the Demographic and Health Surveys (DHS) and the World Bank Living Standards Measurement Surveys (LSMS). The paper is structured as follows. First we present new information from our empirical research on urban/rural differences in food security and child nutritional status, and on socio-economic differentials within area. Then some of the unique features of urban food security and its determinants are highlighted. The paper concludes with a discussion of lessons learned and implications for urban programming.